DIMENSI MOBILITAS PENDUDUK: BERPINDAH, BUKAN UNTUK MENETAP - Haning Romdiati; Mita Noveria (Jurnal Kependudukan Indonesia, 2019)
Significant improvement in information, communication and technology, followed by increased transportation access has made circular mobility much easier. Although circular mobility is not a well-established concept, it refers to repeated migration experiences between origin and destination areas, and there is no intention to stay permanently in any particular destination. This paper aims to assess current types of population mobility, with special focus on circular mobility. Besides literature review, the analysis on this study based on recent studies on population mobility conducted by Research Centre for Population - Indonesian Institute of Sciences. The results show that there is a tendency for increased flow of circular mobility. In general, circular mobility is motivated by occupation and education reasons. Migrant workers still intend to migrate to other destinations that offer better job opportunities. Moreover, students plan to move to origins or move to new destinations after completing their education